LiNi0.29Co0.33Mn0.38O2 polyhedrons with reduced cation mixing as a high-performance cathode material for Li-ion batteries synthesized via a combined co-precipitation and molten salt heating technique - Jiang, X.; Chu, S.; Chen, Y.; Zhong, Y.; Liu, Y.; Shao, Zongping (Elsevier B.V., 2017)
© 2016 Elsevier B.V. Layer-structured LiNi0.29Co0.33Mn0.38O2 as a cathode material for Lithium-ion batteries (LIBs) was synthesized by a facile combined co-precipitation and molten salt heating technique. The effects of precipitate pre-calcination on the morphology, structure and electrochemical performance of the products were investigated systematically. Based on the FESEM, TEM, BET specific surface area and XRD results of the fresh and calcined precipitates, the physically mixed nanoplate-shaped metal hydrates of the fresh precipitate could transform to a spinel-type solid solution with a porous nanoplate morphology after the pre-calcination of the precipitate, demonstrating that the calcined precipitate would provide a larger interfacial reaction area in the second-step reaction, thus facilitating the formation of LiNixCoyMn1-x-yO2 solid solution. The resulting sample LiNi0.29Co0.33Mn0.38O2 prepared by the calcined precipitate (OP-900) at 900 °C showed a first discharge capacity of 177 mA h g-1 at a rate of 0.2 C and a capacity retention of 85.9% after 100 cycles at a rate of 1.0 C, which are higher than those of the similar electrode prepared by the fresh precipitate at the same temperature (HP-900: 165 mA h g-1, 79.3%), due to a reduced cation mixing in the oxide lattice of the OP-900 sample. This phenomenon indicates that the pre-calcination of the precipitate is preferred for the synthesis of LiNixCoyMn1-x-yO2 based on the co-precipitation method.